The action of bed-slope the fish community’s composition of the watercorses on the Zagyva-Tarna watersystem - Szepesi, Zsolt; Harka, Ákos (Acta Agraria Debreceniensis, 2007)
Between 2003 and 2005 faunistic survey was completed in the sections of the low- and highland watercourses of the water-regime of the Zagyva and Tarna rivers. On the basis of bed-slope, dominance and frequency of the fish species the following sections can be divided in the examined streams:1./ Upper-chub-zone: the bed-slope is above 15 m/km. The typical species of this zone – the frequency of these is more then 50%, the dominance is more than 5% – is the Barbatula barbatula, but in the case of bigger streams Leuciscus cephalus is also characteristic.2./ Middle-chub-zone: the bed-slope is between 5-15 m/km. The typical fishspecies–besides the Barbatula barbatula and Leuciscus cephalus – is the Gobio gobio.3./ Down-chub-zone: in the case of larger watercourses (Zagyva and Tarna rivers) the bed-slope is 1,2-5 m/km, at smaller streamlets it is 1,7-5m/km. The typical fishspecies–besides the 3 above mentioned species–are the Cobitis elongatoides, the Alburnus alburnus and in the watersystem of Tarna the Alburnoides bipunctatus.4./ Top-perch-zone: the bed-slope is 0,3-1,2 m/km, or at smaller streamlets it is 0,3-1,7 m/km. The typical fishspecies–besidestheCobitis elongatoides, the Alburnus alburnus and the Alburnoides bipunctatus - are the Rutilus rutilus, the Gobio albipinnatus ant the Rhodeus sericeus.